Cross-sectional study of virological failure and multinucleoside reverse transcriptase inhibitor resistance at 12 months of antiretroviral therapy in Western India. Issue 37 (September 2016) - Karade, Santosh K.; Ghate, Manisha V.; Chaturbhuj, Devidas N.; Kadam, Dileep B.; Shankar, Subramanian; Gaikwad, Nitin; Gurav, Shraddha; Joshi, Rajneesh; Sane, Suvarna S.; Kulkarni, Smita S.; Kurle, Swarali N.; Paranjape, Ramesh S.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The free antiretroviral therapy (ART) program in India has scaled up to register second largest number of people living with HIV/AIDS across the globe. To assess the effectiveness of current first-line regimen we estimated virological suppression on completion of 1 year of ART. The study describes the correlates of virological failure (VF) and multinucleoside reverse transcriptase inhibitor (NRTI) drug resistance mutations (DRMs). In this cross-sectional study conducted between June and August 2014, consecutive adults from 4 State sponsored ART clinics of western India were recruited for plasma viral load screening at 12 ± 2 months of ART initiation. Individuals with plasma viral load >1000 copies/mL were selected for HIV drug resistance (HIVDR) genotyping. Logistic regression analyses were performed to assess factors associated with VF and multi-NRTI resistance mutations. Criteria adopted for multi-NRTI resistance mutation were either presence of K65R or 3 or more thymidine analog mutations (TAMs) or presence of M184V along with 2 TAMs. Of the 844 study participants, virological suppression at 1 year was achieved in 87.7% of individuals. Factors significantly associated with VF ( P  < 0.005) were 12 months CD4 count of ≤100 cells/μL (adjusted OR −7.11), low reported adherence (adjusted OR −4.44), and those living without any partner (adjusted OR −1.98). In patients with VF, the prevalence of non-nucleoside reverse transcriptase inhibitor (NNRTI) DRM (78.75%) were higher as compared to NRTI (58.75%). Multi-NRTI DRMs were present in 32.5% of sequences and were significantly associated with CD4 count of ≤100 cells/μL at baseline (adjusted OR −13.00) and TDF-based failing regimen (adjusted OR −20.43). Additionally, low reported adherence was negatively associated with multi-NRTI resistance (adjusted OR −0.11, P  = 0.015). K65R mutation was significantly associated with tenofovir (TDF)-based failing regimen ( P  < 0.001). The study supports early linkage of HIV-infected individuals to the program for ART initiation, adherence improvement, and introduction of viral load monitoring. With recent introduction of TDF-based regimen, the emergence of K65R needs to be monitored closely among HIV-1 subtype C-infected Indian population.